PELAKSANAAN ASIMILASI NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II KOTABUMI - Ibrahim Fikma Edrisy; Ardi Wijaya Pratama (Universitas Muhammadiyah Kotabumi, 2021)
The assimilation of prisoners must meet certain conditions first which are not regulated in the Correctional Law based on article 14 paragraph (2) which reads that the provisions regarding the requirements and procedures for the implementation of the rights of prisoners as referred to in paragraph (1) shall be further regulated by regulation. The government. The problem in this research is how the assimilation of prisoners in the Class IIa Correctional Institution in Kotabumi is carried out and how is the responsibility of prisoners who receive assimilation. The approach used in this study is an empirical approach, which is an approach that is carried out by conducting direct research to collect all information related to this research, either by interviewing related parties, or by careful observation of the object of research. Based on the results of the study, it can be seen that the Implementation of Prisoners' Assimilation at the Class IIa Penitentiary in Kotabumi, the implementation of an assimilation program for prisoners is needed, looking at Article 7 of the Universal. The implementation of the assimilation program at the Class II a Kotabumi Penitentiary has been running according to applicable procedures and is legal according to law, and from several assimilation theories and the responsibility of prisoners who receive assimilation. According to Article 1 point 4 of the Correctional Law, the role of the Correctional Institution is responsible for all existing prisoner assimilation programs, both in terms of supervision, data collection, and social sanctions carried out by assimilation prisoners who act again within the community itself. The author's suggestion is to carry out assimilation with third parties, this is more effectively done than only in the prison environment. Prisoners who assimilate with third parties will meet more with the community, in contrast to assimilation in the prison environment which only meets visitors and the surrounding community. Assimilation with third parties can be done in Islamic boarding schools, to deepen religious knowledge.